UNDANG – UNDANG PERLINDUNGAN DATA PRIBADI MEMPERKUAT UNDANG – UNDANG PERBANKAN DALAM MENJAGA RAHASIA DATA NASABAH DAN UNTUK MELINDUNGI DATA PRIBADI MASYARAKAT INDONESIA - Katiandagho, Vicky; Diana Darmayanti Putong; Isye Junita Melo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
In this digitalization era, the personal data is something that must be made by all humans, no exeception also for Indonesia people the submission of personal data such as ID cards, email addresses and so on to certain parties to be accessed, allows humans to live an easily, affectively and efficiently life. However, the level of crime that takes advantage of the convenience in the increasingly high digitalization era has forced the country to immediately make rules that regulate, both regulations and sanctions for anyone who unlawfully uses other people’s personal data for profit, which makes Indonesia citizens can live a good life and get legal guarantees regarding the confidentiality of their personal data.